Influence of Personalized Advertising towards Consumer Loyalty: The Mediating Effect of Satisfaction and Moderating Effect of Perceived Quality - dela Peña, Cherrilyn; Ongue, Shulamite; Redo, Arneene Stella; Abellana, Jupert Jasser; Narit, Shiny Rose (International Review of Management and Marketing, 2025)
This study examines the relationship between personalized advertising and consumer loyalty, with a focus on the mediating role of satisfaction and the moderating effects of perceived quality on social media platforms. A quantitative research design was employed, which collected data from 385 respondents in Lanao del Norte, Northern Mindanao, Philippines. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the relationships between personalized advertising, perceived quality, satisfaction, and consumer loyalty. Results indicate that personalized advertising significantly enhances consumer satisfaction, a key driver of loyalty. Respondents exposed to personalized advertisements were more likely to develop stronger brand attachment, with perceived quality as a catalyst in its mediating role. However, perceived quality did not moderate the relationship between personalized advertising and loyalty, suggesting a more direct influence than previously established. The study further highlights that consumer satisfaction is essential for building loyalty, which emphasizes the importance of delivering relevant, high-quality advertisements. These findings highlight the strategic value of personalized advertising in digital marketing. Businesses can use these insights to refine their advertising strategies, enhance customer engagement, and build long-term brand loyalty. Future research should explore the sustained effects of personalized advertising and its impact across different demographic segments.